On Raynaud's phenomena of the upper extremities with special reference to sympathectomy and regeneration of the sympathetic - Katz, Arnold (Department of Surgery, 2020)
Almost 100 percent of Raynaud's Phenomena of the lower extremities respond to surgical treatment. The treatment of Raynaud's Phenomena of the upper extremities, on the other hand, has occupied the attention of medical observers for over fifty years with little success. Surgeons, physicians, research workers, physicists and their associates have attempted to solve the problem and produce a rational solution.